Nonwandering operators in Banach space - Lixin Tian; Jiangbo Zhou; Xun Liu; Guangsheng Zhong (International Journal of Mathematics and Mathematical Sciences)
We introduce nonwandering operators in infinite-dimensional separable Banach space. They are new linear chaotic operators and are relative to hypercylic operators, but different from them. Firstly, we show some examples for nonwandering operators in some typical infinite-dimensional Banach spaces, including Banach sequence space and physical background space. Then we present some properties of nonwandering operators and the spectra decomposition of invertible nonwandering operators. Finally, we obtain that invertible nonwandering operators are locally structurally stable.